(untitled) (Discourse of Law and Administration, 2023)
The author analysed Art. 74a AACP which regulates the issue of electronic service of letters in administrative court procedure in the context of a request for electronic access to case files. The conclusion of the paper is that the legislator made the use of electronic service fully dependent on the express and undoubted consent of a party. Electronic filing of a request for mere access to the case file obligates the administrative court only to provide access to the case file in that form and does not authorise the administrative court to serve the party all correspondence electronically. If, after the case file has been made available in the electronic mode, further correspondence between the administrative court and the party is to be conducted in this mode, then the party should file a separate request referred to in Art. 74a(1)(2) AACP, or the court should request their consent under Art. 74a(1)(3) AACP to use electronic means of service.